2014
DOI: 10.1523/jneurosci.3060-13.2014
|View full text |Cite
|
Sign up to set email alerts
|

NG2-Glia from Pallial Progenitors Produce the Largest Clonal Clusters of the Brain: Time Frame of Clonal Generation in Cortex and Olfactory Bulb

Abstract: NG2-glia are the most unknown population originating in the CNS. Despite their relative abundance in the brain, fundamental questions about their function, heterogeneity, and origin remain in debate. Particularly, it is still intriguing how these cells escaped from classical in vivo clonal analyses describing other neural types. Using StarTrack labeling in mouse brains, we found that NG2-glia are produced as immense clonal clusters whose number of cells is about one order of magnitude higher than in other neur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
48
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(54 citation statements)
references
References 52 publications
6
48
0
Order By: Relevance
“…NG2-glia are highly proliferative and have been shown to produce large clones containing hundreds of cells (Garcia-Marques, Nunez-Llaves, & Lopez-Mascaraque, 2014). Similarly, we observed that the largest clones of Confetti-marked cells were positive for the OL-lineage specific marker SOX10 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…NG2-glia are highly proliferative and have been shown to produce large clones containing hundreds of cells (Garcia-Marques, Nunez-Llaves, & Lopez-Mascaraque, 2014). Similarly, we observed that the largest clones of Confetti-marked cells were positive for the OL-lineage specific marker SOX10 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…4A), similar to the tracing result using PdgfαR-Cre ER / Rosa26YFP (17). Furthermore, a most recent report with a StarTrack-labeled pallial NG2 population suggested that the SVZoriginated NG2 progenitors, although giving rise to the largest clonal oligodendrocyte clusters in the CTX and olfactory bulb, lack astroglial potential in vivo (27). This indicated that NG2…”
Section: Postnatal Svz Gfapmentioning
confidence: 99%
“…Although NG2 cells remain proliferative throughout life, their cell cycle time lengthens significantly with age (Psachoulia et al, 2009; Young et al, 2013). However, it is noteworthy that significant clonal expansion of NG2 cells has been detected between P120 and P240 (Garcia-Marques, 2014). Similarly, the rate of oligodendrocyte differentiation and NG2 cell proliferation are greater in white matter than in gray matter (Young et al, 2013; Hill et al, 2013).…”
Section: Age-dependent Changes In Ng2 Cell Fatementioning
confidence: 99%